The Green Strategic Orientation and Competitive Advantage: The Role of Stakeholder Pressure and Institutional Environment - Puput Aryanto; Seno Hadi Saputro (Fakultas Ekonomi dan Bisnis, Universitas Palangka Raya, 2026)
Objective – This study investigates how Green Strategic Orientation (GSO) shapes competitive advantage, with particular attention to the concurrent moderating effects of stakeholder pressure and institutional environment within an emerging economy setting. Design/Methodology/Approach – Drawing on the Natural Resource-Based View (NRBV) and Institutional Theory in an integrated framework, this work fills a gap in the existing literature where both moderating factors have been studied in isolation rather than tested together within a unified boundary condition analysis. Using a quantitative cross-sectional survey of 200 firms spread across four industry sectors in the Bangka Belitung Islands, Indonesia, data were analyzed through PLS-SEM with 5,000 bootstrap resamples. Findings – The results confirm that GSO exerts a positive influence on competitive advantage (β = 0.38; f² = 0.21; p < 0.001; R² = 0.54), with both stakeholder pressure (β = 0.19; p = 0.002) and institutional environment (β = 0.17; p = 0.005) meaningfully amplifying this effect. Simple slope analysis further shows that the GSO impact rises from β = 0.22 to β = 0.51 when stakeholder pressure is high, and from β = 0.21 to β = 0.49 when institutional conditions are supportive. These results hold consistently across alternative model specifications. Implications – This work represents the first empirical test of simultaneous dual moderation within an integrated NRBV–Institutional Theory framework, highlighting that firms need to cultivate internal green capabilities while actively engaging with both their stakeholders and institutional environments to fully realize competitive gains.